COMPOSITIONAL ANALYSIS OF RAW MATERIALS IN SORBENT PRODUCTION - Nomonova, Zilola; Jumayeva, Dilnoza; Zaripbaev, Kunkhoja; Oxunjonov, Zuxriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the results of obtaining an adsorbent based on carbon-containing soot waste through chemical activation using hydrochloric acid and sodium hydroxide. As a result, improvements were achieved in the compositional purity of the material and its sorption properties. Data are presented on the elemental and oxide composition of the waste after chemical activation, which enables a reduction in reagent consumption and the removal of harmful compounds prior to subsequent activation stages. The analytical characteristics of the resulting sorption-active adsorbent are substantiated.